Riches of the forest: for health, life and spirit in Africa - López, C.; Shanley, P. (Center for International Forestry Research, 2004)
This volume brings to life 19 case studies featuring forest plants and animals. The botanical cases are presented according to the main part of the plant being used - the fruit, bark, roots or wood. Sometimes the plants have multiple uses, or different cultures may use the same part of a particular plant in different ways. Animals and animal products that require forest habitat are also critical for rural livelihoods, and are represented in this volume by bush meat and weevil larvae. In each case, the contributors describe the main characteristics of the forest product, its historical usage, harvesting and management, and how it is processed and traded. In closing, each author comments briefly on trends and current issues regarding the resource. The final chapter reviews common themes and lessons that can be drawn from these cases.